2011
DOI: 10.1001/archneurol.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Braking Signals During Inflammation

Abstract: Background: In a recent genome-wide transcriptional analysis, we identified a gene signature for multiple sclerosis (MS), which reverted back to normal during pregnancy. Reversion was particularly evident for 7 genes: SOCS2, TNFAIP3, NR4A2, CXCR4, POLR2J, FAM49B, and STAG3L1, most of which encode negative regulators of inflammation.Objectives: To corroborate dysregulation of genes, to evaluate the prognostic value of genes, and to study modulation of genes during different treatments.Design: Comparison study.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…In contrast, expression of the SOCS2 gene [29], which acts as a negative regulator of TLR-induced DC activation, was down-regulated. Defects in negative-feedback loops regulating inflammation lead to increased inflammation-sensitive autoimmune diseases [30]. Thus, the alterations in Unc93B1 and SOCS2 may result in an enhancement of TLR activation-associated inflammation [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, expression of the SOCS2 gene [29], which acts as a negative regulator of TLR-induced DC activation, was down-regulated. Defects in negative-feedback loops regulating inflammation lead to increased inflammation-sensitive autoimmune diseases [30]. Thus, the alterations in Unc93B1 and SOCS2 may result in an enhancement of TLR activation-associated inflammation [31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of three of these genes encoding negative regulators of inflammation has been inversely correlated with relapse rate and EDSS in men and women in the initial phase of relapsing remitting MS [96]. …”
Section: Reproductive Eventsmentioning
confidence: 99%
“…These results suggested that endometriosis has disparate effects on proteinase production by uterine tissue as compared to the peritoneum, which is consistent with cell-type specific actions and possibly proximal vs. distal influences of the disease milieu. The function of FAM49B has yet to be elucidated, but it has been associated with diseases that are related to immune dysregulation, such as multiple sclerosis [61]. Interestingly, immune dysfunction has also been implicated in the pathogenesis of endometriosis [16].…”
Section: Discussionmentioning
confidence: 99%